Liquid Metal Patterning and Unique Properties for Next‐Generation Soft Electronics (Adv. Sci. 6/2023). Issue 6 (24th February 2023) - Kim, Minwoo; Lim, Hyungjun; Ko, Seung Hwan
Abstract : Soft Electronics In article number 2205795, Seung Hwan Ko and co‐workers aim to provide thorough knowledge about patterning methods and unique properties for liquid metal (LM)‐based future soft electronics. It is expected to bring advancements in future soft electronics owing to its conductivity, conformability, stretchability, and biocompatibility. Since there are numerous LM patterning methods, this review helps to choose an appropriate patterning method based on comprehensive understanding.